Can Pro-growth Policies Lift all Boats? An Analysis Based on Household Disposable Income - Causa, Orsetta (OECD Economics Department Working Papers, 2015)
In a majority of OECD countries, GDP growth over the past three decades has been associated with growing income disparities. To shed some lights on the potential sources of trade-offs between growth and equity, this paper investigates the long-run impact of structural reforms on GDP per capita and household income distribution. Pro-growth reforms can be distinguished according to whether they are found to generate an increase or a reduction in household disposable income inequality. Those that contribute to reduce inequality include the reduction in regulatory barriers to competition, trade and FDI, as well as the stepping-up in job search assistance and training programmes. Conversely, a tightening of unemployment benefits for the long-term unemployed is found to lift mean household income but to lower income among poorer households, thus raising inequality. Several other reforms have no significant impact on income distribution